+0  
 
0
304
1
avatar+4 

If 𝑥 + 𝑦 = 5 and 𝑥𝑦 = −3, then 𝑥2 + 𝑦2 is equal to

Skylion  Jun 10, 2017
 #1
avatar+26753 
+1

We have  \((x+y)^2=x^2+y^2+2xy\)

 

So  \(x^2+y^2=(x+y)^2-2xy\)

 

Here:  \(x^2+y^2=5^2-2(-3)\text{ ... or ... }x^2+y^2=25+6\rightarrow31\)

 

 

.

Alan  Jun 10, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.